Analisis Pengaruh Persepsi Harga, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian (Studi Pada Konsumen Sari Roti di Kota Semarang) - Agus Budi Purwanto; Hendro Budhi Risaputro (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
Abstract The purpose of this study was to analyze the influence of Price Perception, Product Quality and Brand Image on Purchasing Decisions on Sari Roti consumers in Wonodri Village Semarang. The population in this study were all consumers who bought Sari Roti in Indomart. The sample is 130 people. The sampling technique used is stratified proportional sampling. The data analysis tool used in this study is multiple regression analysis. Based on the results of the study: There is a positive and significant influence between Price Perception on Purchasing Decisions, There is a positive and significant influence between Product Quality on Purchasing Decisions, There is a positive and significant influence between Brand Image on Purchasing Decisions, Simultaneously there is a positive and significant effect between Price Perception , Product Quality and Brand Image on Purchasing Decisions. Keywords: Price Perception, Product Quality, Brand Image, Purchasing Decision